Kidney transplant recipients switching to prolonged-release tacrolimus: five-year real-world clinical outcomes from the CHORUS study - Kamar, Nassim; Kóbori, László; Lemoine, Mathilde; Nemes, Balazs; Lee, Su Hyung; An, Ha Phan Hai; Watarai, Yoshihiko; Yang, Jaeseok; Han, Seungyeup; Kuypers, Dirk; Krämer, Bernhard; Blogg, Martin; et al. (Annals of transplantation, 2025)
Tacrolimus trough-level concentration variability and patient non-adherence are risk factors for poorer graft and patient survival. This study investi...